Mauritius Financial Sector Assessment Program : IAIS Insurance Core Principles - World Bank (World Bank, Washington, DC, 2017)
This assessment focused on the supervision and regulation of the insurance sector and the role of the Financial Services Commission (FSC) in Mauritius. The FSC has responsibility for licensing and supervision of all players in the insurance market-insurance companies, distributors; loss adjusters; reinsurance companies; reinsurance brokers, and actuaries and auditors. This report relates to a dedicated assessment mission conducted in July 2011. The FSC maintains a fairly detailed website that contains copies of relevant laws and regulations applicable to insurance companies in Mauritius. Also available on the website are copies of guidelines of general application that have been issued to the insurance companies, statistics of the industry's performance, and copies of the annual reports issued by FSC. In addition to its discussions with FSC personnel, mission members met with representatives of the trade association and with executives of a representative sample of companies, both life and general insurance, operating in the market. Other contacts included brokers and auditors. The insurance sector in Mauritius is material although not fully developed in terms of size. Insurance premium stands at MUR 17.5 billion represented at 68 percent life and 32 percent non-life insurances. Life insurance growth has been more impressive than non-life insurance performance. Although both segments have shown healthy nominal growth rates, real growth has been less spectacular for the non-life sector. Interpreting non-life sector premium performance can be confused by global pricing cycles.